Surviving Deadly Lung Infections: Innate Host Tolerance Mechanisms in the Pulmonary System - Crane, Meredith J.; Lee, Kayla M.; FitzGerald, Ethan S.; Jamieson, Amanda M. (Frontiers in Immunology, 2018)
Much research on infectious diseases focuses on clearing the pathogen be it through the use of antimicrobial drugs, the immune response, or a combination of both. Rapid clearance of pathogens allows for a quick return to a healthy state and increased survival. Pathogen-targeted approaches to combating infection have inherent limitations including their pathogen-specific nature, the potential for antimicrobial resistance, and poor vaccine efficacy, among others. Another way to survive an infection is to tolerate the alterations to homeostasis that occur during a disease state through a process called host tolerance or resilience, which is independent from pathogen burden. Alterations in homeostasis during infection are numerous and include tissue damage, increased inflammation, metabolic changes, temperature changes, and changes in respiration. Given its importance and sensitivity, the lung is a good system for understanding host tolerance to infectious disease. Pneumonia is the leading cause of death for children under 5 worldwide. One reason for this is because when the pulmonary system is altered dramatically it greatly impacts the overall health and survival of a patient. Targeting host pathways involved in maintenance of pulmonary host tolerance during infection could provide an alternative therapeutic avenue that may be broadly applicable across a variety of pathologies. In this review we will summarize recent findings on tolerance to host lung infection. We will focus on the involvement of innate immune responses in tolerance. In particular, how an initial viral lung infection may alter tolerance mechanisms in leukocytic, epithelial, and endothelial compartments to a subsequent bacterial infection will be addressed. By understanding tolerance mechanisms in the lung we can better address treatment options for deadly pulmonary infections.